Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3173963
|View full text |Cite
|
Sign up to set email alerts
|

Prayana

Abstract: We describe the design of a novel mobile phone-based application for loan management in a resource-constrained setting. In this setting, a social enterprise manages autorickshaw loans for drivers, taking charge of collections. The design was informed by an ethnographic study which revealed how loan management for this financially vulnerable population is a daily struggle, and loan payment is a collaborative achievement between collectors and drivers. However, drivers and collectors have limited resources to-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The broad themes of the wider engagement were to understand the impact of platform work and digital money on this population, and to support the organisations working with these drivers [e.g. Mehra et al 2018, Muralidhar et al 2018]. This long-term community engagement and partnership enabled us to conduct the follow-up study reported here.…”
Section: Methodsmentioning
confidence: 99%
“…The broad themes of the wider engagement were to understand the impact of platform work and digital money on this population, and to support the organisations working with these drivers [e.g. Mehra et al 2018, Muralidhar et al 2018]. This long-term community engagement and partnership enabled us to conduct the follow-up study reported here.…”
Section: Methodsmentioning
confidence: 99%
“…In an attempt to further bridge some of the aforementioned sociotechnical gaps, intermediation, or the use of technology with the help of a trusted, local agent, has shown promise in resourceconstrained areas [81,82]. Intermediation has been applied to more effectively engage low-literate users [41,48,49,88]; motivate trying new services [76,77]; facilitate sustained use [33]; and enable those with indirect access to technology to benefit from applications [67].…”
Section: Technologies For Agricultural Informationmentioning
confidence: 99%
“…Some technologies are built specifically with intermediation as the predominant use case, conferring the "primary user" label to the intermediary [38,49,65,68,90]. For example, Rahman et al [75] show that small businesses can serve as ICT intermediaries, and that engagement with the small business owners can be extended to engagement with the ICT.…”
Section: Technologies For Agricultural Informationmentioning
confidence: 99%
“…Vyas et al 's ethnographic study of household finances [42] for instance, noted the "artful and creative ways people incorporate their social lives into financial activities". The work of Kaye, Vyas and Vines [15,[40][41][42] among others working across cultural contexts [2,17,23] also highlights how new technologies can often flatten out or overlook many of these important distinctions and nuances in how money is actually used. Zelizer [45] offers a conceptual framing for such reflections.…”
Section: Related Work Hci and Financial Technologiesmentioning
confidence: 99%